2010
DOI: 10.1175/2010waf2222340.1
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Precipitation Regimes Associated with the Sea Breeze and Land Breeze in Southern Mississippi and Eastern Louisiana

Abstract: This study assesses the monthly climatology of the timing and placement of convective precipitation events induced by sea and land breezes in the Louisiana-Mississippi-Alabama region, and determines possible reasons for the monthly differences. These objectives were achieved through surface wind climatologies and radar composites from 2003 to 2005, supplemented by statistically significant tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
(27 reference statements)
1
22
1
Order By: Relevance
“…It is interesting to note that the highest average precipitable water (49.10 mm for 1-60°during [2003][2004][2005][2006][2007] was also associated with one of the lowest average rainfall gauge precipitation totals (4.83 mm or 0.19 inches for 1-60°) ( Table 2). These findings are inconsistent with those of previous research reported above (Dostalek & Schmit, 2001;Hill et al, 2010), but may be due to a more stable air mass.…”
contrasting
confidence: 99%
“…It is interesting to note that the highest average precipitable water (49.10 mm for 1-60°during [2003][2004][2005][2006][2007] was also associated with one of the lowest average rainfall gauge precipitation totals (4.83 mm or 0.19 inches for 1-60°) ( Table 2). These findings are inconsistent with those of previous research reported above (Dostalek & Schmit, 2001;Hill et al, 2010), but may be due to a more stable air mass.…”
contrasting
confidence: 99%
“…Elevated lightning frequencies are observed along the coastlines of the Gulf Coast states and northward up to North Carolina. The primary driver for this enhancement is land-and sea breeze-driven convergence zones creating favorable thunderstorm updraft environments [e.g., Hill et al, 2010]. The high spatial resolution of this climatology reveals an exponential decline in the percentage of CONUS area with higher lightning frequencies ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Convection and convergence of low-level winds associated with the sea breeze can increase cloud production and precipitation across the region (e.g., Hill et al 2010;Azorin-Molina et al 2014). Abnormally high temperatures often influence the local and regional winds, which in return modify mesoscale circulations such as the sea breeze.…”
Section: Introductionmentioning
confidence: 99%